Direct observation of cation-exchange in liquid-to-solid phase transformation in FA1−xMAxPbI3 based perovskite solar cells. Issue 19 (30th April 2018) - Xie, Yue-Min; Yu, Binbin; Ma, Chunqing; Xu, Xiuwen; Cheng, Yuanhang; Yuan, Shuai; Wang, Zhao-Kui; Chandran, Hrisheekesh Thachoth; Lee, Chun-Sing; Liao, Liang-Sheng; Tsang, Sai-Wing
Abstract : Organic-cation-exchange in liquid-to-solid phase transformation in FA1− x MA x PbI3 based perovskite solar cells. Abstract : Mixed-organic-cation FA1− x MA x PbI3 perovskites are currently attracting intensive attention for their high photovoltaic performance. However, FA1− x MA x PbI3 usually has an undesired non-perovskite phase leading to a compromised efficiency, and a facile strategy to achieve pure-phase FA1− x MA x PbI3 has been rarely reported. Here, we demonstrate a facile approach to form δ-phase free FA1− x MA x PbI3 using a non-stoichiometric precursor solution. It is found that a small amount of excess methylammonium iodide (MAI) added to the precursor solution has a profound effect on perovskite crystallization during the liquid-to-solid phase transformation. Using an in situ photoluminescence spectroscopy measurement, it is found that the excess MAI can promote the formation of FA1− x MA x PbI3 and facilitate the cation-exchange between organic FA + and MA + during the film formation. Based on the optimized pure-phase FA1− x MA x PbI3, the perovskite solar cells exhibit an encouraging power conversion efficiency (PCE) of 17.40%. This study demonstrates a facile method to achieve high performance FA dominating mixed-organic-cation perovskite devices while providing insight into the ion-exchange process during perovskite crystallization.